О деформировании системы «крепь-массив» в условиях слоистых пород глубоких шахт - Халимендик, Ю.М.; Барышников, А.С.; Халимендик, В.Ю. (Наукові праці УкрНДМІ НАН України, 2014)
Викладено механізм деформування системи «кріплення-масив» виробок глибоких шахт. Наведено результати натурних спостережень за вдавлюванням стійок кріплення в підошву виро-бок. Обгрунтовано необхідність застосування підп'ятників під стійки рамного кріплення в умовах порід середньої міцності. The mechanism of deforming of the "support-rock massif" system of mine workings in deep mines is developed. The results of in-situ observations over the support racks penetration into the floor of work-ings are presented. Necessity of application of end-thrust bearings with racks of arch support under the conditions of medium-hard rock is substantiated.